Aplikasi Pengelola Keuangan Pribadi Berbasis Android dengan Pendekatan User Centered Design (UCD) - Triwidadi, Kurniawan Adhisukma; Widodo, Tri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Financial management plays a very important role in everyday life. Proper management can help one in organizing and controlling expenses. In the process of financial management, people should prioritize basic needs first. However, it is often difficult to distinguish between primary, secondary, and additional needs, which ultimately risks creating a consumptive culture, which is the habit of buying things that are not really needed. One solution to overcome this is to design an application that can help manage finances, equipped with features that limit spending if it exceeds the balance of income or if non-primary expenses exceed 20% of total income. In this research, the approach used is User Centered Design (UCD) which focuses on meeting the needs of users in using the application. The application was also tested using the Black Box method and obtained a 100% success percentage. The features of classifying and recording needs greatly facilitate users in managing finances. The results of the study can provide benefits for users in managing finances, especially in managing primary needs, so that they can manage finances more effectively.